2017
DOI: 10.1007/s13197-017-2651-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of phenolics in Syzygium cumini seed and their modulatory role on tertiary butyl-hydrogen peroxide-induced oxidative stress in H9c2 cell lines and key enzymes in cardioprotection

Abstract: The study quantified the major phenolics in different fractions of seeds and evaluated their cardioprotective efficacy. Gallic acid, ellagic acid, cinnamic acid, quercetin, syringic acid and ferulic acid were the major polyphenols present in different fractions of seeds. The cardioprotective effect of seed fractions in modulating angiotensin converting enzyme (ACE), HMG-CoA reductase, LDL oxidation and tertiary butyl hydrogen peroxide (TBHP) induced oxidative stress in H9c2 cardiac cell lines were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…Syama et al . () reported that jambolan seed extract (obtained sequentially using hexane, ethyl acetate, methanol and water as solvents) effectively reduced the oxidative stress in H9c2 cell lines. Moreover, the extract fractions possessed inhibitory action against LDL oxidation and different enzymes (angiotensin‐converting enzyme and HMG‐CoA reductase).…”
Section: Health‐promoting Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Syama et al . () reported that jambolan seed extract (obtained sequentially using hexane, ethyl acetate, methanol and water as solvents) effectively reduced the oxidative stress in H9c2 cell lines. Moreover, the extract fractions possessed inhibitory action against LDL oxidation and different enzymes (angiotensin‐converting enzyme and HMG‐CoA reductase).…”
Section: Health‐promoting Activitiesmentioning
confidence: 99%
“…The antihypertensive effect of jambolan leaf extract might be due to the presence of flavonoids in jambolan leaf extract, as they have role in inhibition of arterial tone by the blockade of extracellular calcium influx (Ribeiro et al, 2014). Syama et al (2017) reported that jambolan seed extract (obtained sequentially using hexane, ethyl acetate, methanol and water as solvents) effectively reduced the oxidative stress in H9c2 cell lines. Moreover, the extract fractions possessed inhibitory action against LDL oxidation and different enzymes (angiotensin-converting enzyme and HMG-CoA reductase).…”
Section: Antihyperlipidaemic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Kaempferol, rutin, luteolin, quercetin, resveratrol Activity against doxorubicin-induced cardiotoxicity [119] Gallic, ellagic, syringic, ferulic, cinnamic acids, and quercetin Attenuate oxidative stress in H9c2 cardiomyoblasts [120] Aspalathin and phenylpyruvic acid-2-O-β-D-glucoside Protect myocardial infarction caused by chronic hyperglycemia [121] Puerarin…”
Section: Cardioprotective Activitymentioning
confidence: 99%
“…The seeds of the plant contain various phytoconsitutents such as alkaloid, jambosine, and glycoside jambolin or antimellin . In vivo S. cumini is shown to have antimicrobial, antidiabetic, and antioxidant cardioprotective antiobesity properties. In vitro context, cytotoxic effect of S. cumini has been reported in breast cancer cell line .…”
Section: Introductionmentioning
confidence: 99%